The Use of a Simple Three-Level Bronchoscopic Assessment of Inhalation Injury to Predict in-Hospital Mortality and Duration of Mechanical Ventilation in Patients with Burns. Issue 1 (January 2018) - Aung, M. T.; Garner, D.; Pacquola, M.; Rosenblum, S.; McClure, J.; Cleland, H.; Pilcher, D. V.
Major burn centres in Australia use bronchoscopy to assess severity of inhalation injuries despite limited evidence as to how best to classify severity of inhalational injury or its relationship to patient outcomes. All patients with burns who were admitted to the intensive care unit (ICU) at The Alfred Hospital between February 2010 and July 2014 and underwent bronchoscopy to assess inhalational injury, were reviewed. Age, total body surface area burnt, severity of illness indices and mechanisms of injury were extracted from medical histories and local ICU and burns registries. Inhalational injury was classified based on the Abbreviated Injury Score and then grouped into three categories (none/mild, moderate, or severe injury). Univariable and multivariable analyses were undertaken to examine the relationship between inhalational injury and outcomes (in-hospital mortality and duration of mechanical ventilation). One hundred and twenty-eight patients were classified as having none/mild inhalational injury, 81 moderate, and 13 severe inhalation injury. Mortality in each group was 2.3% (3/128), 7.4% (6/81) and 30.7% (4/13) respectively. Median (interquartile range) duration of mechanical ventilation in each group was 26 (11–82) hours, 84 (32–232) hours and 94 (21–146) hours respectively. After adjusting for age, total body surface area burnt and severity of illness, only the severe inhalation injury group was independently associated with increased mortality (odds ratio 20.4 [95% confidence intervals CI 1.74 to 239.4], P=0.016). Moderate inhalation injury was independently associated with increased duration of ventilation (odds ratio 2.25 [95% CI 1.53 to 3.31], P <0.001), but not increased mortality. This study suggests that stratification of bronchoscopically-assessed inhalational injury into three categories can provide useful prognostic information about duration of ventilation and mortality. Larger multicentre prospective studies are required to validate these findings.